Dangir-Tech: Inovasi Mekanisasi Pertanian untuk Meningkatkan Efisiensi Petani Jagung pada Proses Pendangiran - Widiyanti Widiyanti; Mardji Mardji; Erwin Komara Mindarta; Muhammad Idris Effendi; Fahru Riza; Lailatul Nurjanah (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
The issue of manual tillage still practiced by maize farmers in Wonosari Village results in low work efficiency and high occupational health risks. This community service project aims to introduce appropriate technology in the form of the Dangir-Tech machine as a mechanized solution for soil cultivation. The implementation involved site surveys, equipment design and development, operational training, and ongoing evaluation. Results indicate that Dangir-Tech improved work efficiency by over 40%, reduced physical fatigue, and was well-received by farmers. Satisfaction evaluation showed that more than 90% of respondents were in the satisfied to highly satisfied categories. The application of this technology successfully fostered healthier and more productive farming practices. These findings highlight the importance of farmer-oriented local innovations in promoting agricultural modernization in rural areas.